Occurrence of Culicoides Latreille (Diptera: Ceratopogonidae) Collected from a Layer Farm in Yogyakarta - Prastowo, Joko; Wulandari, Kartika Yuga; Nugraheni , Yudhi Ratna; Priyowidodo, Dwi; Sahara, Ana (International Journal of Poultry Science, 2018)
Background and Objective: Culicoides spp. compose the most studied vector genera and contain the species that is a vector of Leucocytozoon, the parasite that causes leucocytozoonosis. One hundred species of Culicoides spp. inhabit Indonesia and are scattered among 19 provinces, with great diversity in each region. The aim of this research was to study the species diversity and the dominance of Culicoides on layer farms. Methodology: Midges were obtained from layer farms in Sentolo, Kulon Progo (altitude ±78 m); Pakem, Sleman (altitude ±371 m) and Cangkringan, Sleman (altitude ±745 m). Midges were collected using a light trap (New Jersey Standard #2858) for 12 h, from 6 pm-6 am. Identification was performed using dissecting microscope and classified using the identification key of Wirth and Hubert. Results: Eight species were found in this study: Culicoides arakawae, C. huffi, C. oxystoma, C. guttifer, C. sumatrae, C. peregrinus, C. palpifer and C. fulvus. There was diversity in the species collected from the three research areas. Culicoides arakawae was the dominant species found in Sentolo; in Pakem, the most collected species was C. huffi and in Cangkringan, it was C. fulvus. Conclusion: There was a difference in the number of midges collected from the areas with differing topography. The largest collection of Culicoides (270 midges) was obtained from Sentolo subdistrict, Kulon Progo Regency.